Impact of US unconventional monetary policy on dynamic stock-bond correlations: Portfolio rebalancing and signalling channel effects - Gokmenoglu, Korhan K.; Hadood, Abobaker Al Al (Academic Press Inc Elsevier Science, 2020)
This paper investigates the impacts of both the portfolio rebalancing and signalling channel effects associated with US unconventional monetary policy on the dynamic correlation between the stock and bond markets at different levels of stock-bond market correlation distributions. The empirical results reveal that the portfolio rebalancing channel has a strong and predominantly negative effect on the dynamic stock-bond market correlations. In contrast, the signalling channel positively affects the dynamic stock-bond market correlations. The results also provide evidence of an asymmetric effect at the lower quantiles. These findings hence provide valuable information for policymakers, traders and portfolio managers.
Keywords: Dynamic stock-bond market correlations; Portfolio rebalancing and signalling channels; Quantile regression